GENEOLOGI INTELEKTUAL ULAMA AWAL ABAD XX DI KABUPATEN BULUKUMBA DAN BANTAENG SULAWESI SELATAN - Wardiah Hamid (Balai Penelitian dan Pengembangan Agama Semarang, 2019)
After the opening of the Suez Canal in the early twentieth century, Muslims in the archipelago massively carried out pilgrimage (Hajj) as well as deepening religious knowledge in Mecca and Medina. This had an impact on the emergence of Muslim clerics (ulama) from the archipelago who took part in both cities and returned to their homeland. These ulama are scholarly interconnected, when they were studying in the holy land and doing missionary (da'wah) in their hometowns. This article reveals the history of intellectual genealogy of the twentieth century of Bugis scholars in the districts of Bulukumba and Bantaeng, South Sulawesi. This study uses a historical approach and the data collected through interview, documentation, and observation. The results showed that, first, the history of intellectual genealogy of Muslim scholars in the early twentieth century in Bulukumba and Bantaeng was formed when the socio-political dynamics of the Middle East in 1920 over the victory of Ibn Saud became a revival symbol for the Wahabi group impacted by the arrival of the Ahlul Sunnah wal Jamaah scholars to the Archipelago. The return of the knowledge seekers had a positive impact on the development of the transmission of religious knowledge to local people who wanted to gain knowledge from these scholars. Second, the figures of the early twentieth century scholars in Bulukumba and Bantaeng eventually formed intellectual geneology between teacher and pupil. The transfer of religious knowledge at that time was carried out at variety of venues: houses, mosques (mushala) which also functioned as a place of worship and for the learning process.